Food, conviviality and the work of mourning. The asado scandal at Argentina's ex-ESMA - Sosa, Cecilia (2016)
This article addresses a controversial debate raised by an asado-party, which was celebrated by the end of 2012 at the former Navy Mechanics School (ESMA), the main clandestine detention centre where almost 5,000 people were held captive and tortured during Argentina’s last dictatorship (1976-1983). In 2004, the former school was transformed into a “space of memory”. Drawing upon the asado episode, I consider which kind of practices of re-occupation former landscapes of death may allow. I first provide an overview of the interventions that took place at ESMA within the Kirchnerist period (2003-2015). Second, I bring into play some cultural productions of the new generations, as well as performances and philosophical ruminations regarding the asado as a main theme in the local culture. Finally, I put these materials in the larger context of memory politics to explore how food-reunions – and expanded tables might work as a public pathway for a collective digestion of grief. The question that is ultimately at stake is how to kindle alternative hospitalities and dialogues in landscapes marked by loss. Might the spectrum of activities that took place at the former ESMA during the Kirchnerist years suggest a new conviviality for the aftermath of violence?